Epileptologists telling their experiences caring for patients with epilepsy. (February 2021) - Chesi, P.; Marini, M.G.; Scarlata, P.; Mecarelli, O.; ,; Aguglia, U.; Assenza, G.; Audenino, D.; Benna, P.; Bilo, L.; Boero, G.; Costa, C.; et al.
Highlights: Patients' everyday-life and caregiver burden affect the epilepsy care pathway. The attentive relationship of care was found to be the main element of coping. Narrative medicine allowed the health professionals to express their inner dilemma. Abstract: Objective: This research was focused on expert professionals in epilepsy care to understand their points of view on the care pathway and their living relationships with patients. Methods: Researchers prepared a semi-structured parallel chart and distributed it online among 21 Italian centres of care. Each health professional was prompted to write five narratives on cases of patients with epilepsy, subsequently analysed through narrative medicine methods. Next, a consensus meeting was held, to individualise an action plan based on the narratives. Results: Ninety-one parallel charts were collected from 25 epileptologists, who had a mean age of 50 years; their narratives concerned patients with a mean age of 37 years, with different types of epilepsy (53 % drug-resistant; 31 % unemployed). The limitations in the daily life of people with epilepsy (57 %), employment (42 %), caregiver burden (51 %), and the universal prevalence of fear were the primary topics that emerged. Attentive and reassuring care relationships were found to be the main element of coping (21 %). A new multi-factorial classification of epilepsies, integrating clinical with social and legal risk factors, was the main agreed action to face the issues identified. Conclusions: The narrative medicine approach supplied a broader scenario of living with epilepsy, including the family and social impact and possible effects on the choices for care pathways. The epileptologists showed a strong motivation to care for patients with epilepsy and deep involvement in the care relationships; the use of parallel chart demonstrated to be an effective tool to preserve their wellbeing.